Distinct roles of hand2 in developing and adult autonomic neurons. Issue 10 (15th February 2016) - Stanzel, Sabine; Stubbusch, Jutta; Pataskar, Abhijeet; Howard, Marthe J.; Deller, Thomas; Ernsberger, Uwe; Tiwari, Vijay K.; Rohrer, Hermann; Tsarovina, Konstantina
ABSTRACT: The bHLH transcription factor Hand2 is essential for the acquisition and maintenance of noradrenergic properties of embryonic sympathetic neurons and controls neuroblast proliferation. Hand2 is also expressed in embryonic and postnatal parasympathetic ganglia and remains expressed in sympathetic neurons up to the adult stage. Here, we address its function in developing parasympathetic and adult sympathetic neurons. We conditionally deleted Hand2 in the parasympathetic sphenopalatine ganglion by crossing a line of floxed Hand2 mice with DbhiCre transgenic mice, taking advantage of the transient Dbh expression in parasympathetic ganglia. Hand2 elimination does not affect Dbh expression and sphenopalatine ganglion size at E12.5 and E16.5, in contrast to sympathetic ganglia. These findings demonstrate different functions for Hand2 in the parasympathetic and sympathetic lineage. Our previous Hand2 knockdown in postmitotic, differentiated chick sympathetic neurons resulted in decreased expression of noradrenergic marker genes but it was unclear whether Hand2 is required for maintaining noradrenergic neuron identity in adult animals. We now show that Hand2 elimination in adult Dbh ‐expressing sympathetic neurons does not decrease the expression of Th and Dbh, in contrast to the situation during development. However, gene expression profiling of adult sympathetic neurons identified 75 Hand2 ‐dependent target genes. Interestingly, a notable proportion of down‐regulated genes (15%) encode for proteins with synaptic and neurotransmission functions. These results demonstrate a change in Hand2 target genes during maturation of sympathetic neurons. Whereas Hand2 controls genes regulating noradrenergic differentiation during development, Hand2 seems to be involved in the regulation of genes controlling neurotransmission in adult sympathetic neurons. © 2016 Wiley Periodicals, Inc. Develop Neurobiol 76: 1111–1124, 2016